Alarmin’ Immunologists: IL-33 as a Putative Target for Modulating T Cell-Dependent Responses - Gajardo Carrasco, Tania; Morales, Rodrigo A.; Pérez, Francisco; Terraza, Claudia; Yáñez, Luz; Campos-Mora, Mauricio; Pino-Lagos, Karina (Frontiers in Immunology, 2015)
IL-33 is a known member of the IL-1 cytokine superfamily classically named ‘atypical’ due to its diverse functions. The receptor for this cytokine is the ST2 chain (or IL-1RL1), part of the IL-1R family, and the accessory chain IL-1R. ST2 can be found as both, soluble and membrane-bound forms, property that explains, at least in part, its wide range of functions. IL-33 has increasingly gained our attention as a potential target to modulate immune responses. At the beginning known as one of the participants during the development of allergic states, and other Th2-mediated responses, it is now accepted that IL-33 contributes to Th1-driven pathologies as demonstrated in animal models of experimental autoimmune encephalomyelitis (EAE), collagen-induced arthritis (CIA), trinitrobenzene sulfonic acid (TNBS)-induced experimental colitis, among others. Interestingly, current data is placing IL-33 as a novel regulator of immune tolerance by affecting regulatory T cells (Tregs), although the mechanism is not fully understood, it seems that Dendritic cells (DCs) and Myeloid Suppressor-derived cells (MDSC) maybe cooperating in the generation and/or establishment of IL-33-mediated tolerance. Here, we review the most updated literature on IL-33, its role on T cell biology and its impact in immune tolerance.